2018
DOI: 10.3390/neuroglia1020022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemically-Functionalized Single-Walled Carbon Nanotubes on the Morphology and Vitality of D54MG Human Glioblastoma Cells

Abstract: The unique properties of single-walled carbon nanotubes (SWCNTs) have made them interesting candidates for applications in biomedicine. There are diverse chemical groups that can be attached to SWCNTs in order for these tiny tubes to gain various functionalities, for example, water solubility. Due to the availability of these “functionalization” approaches, SWCNTs are seen as agents for a potential anti-cancer therapy. In this context, we tested different chemically-functionalized forms of SWCNTs to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Hopkins et al demonstrated the application of chemically functionalized carbon nanotubes (CNTs) against GBM. In this work, tetrahydrofurfuryl-terminated polyethylene glycol (PEG-THFF) attached to the surface of CNTs not only increased the solubility of carbon-based NPs in water, but it also reduced the proliferation rate of D54MG cells (human glioblastoma cells) while increasing the rate of cell death [68].…”
Section: Therapeutic Functionalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Hopkins et al demonstrated the application of chemically functionalized carbon nanotubes (CNTs) against GBM. In this work, tetrahydrofurfuryl-terminated polyethylene glycol (PEG-THFF) attached to the surface of CNTs not only increased the solubility of carbon-based NPs in water, but it also reduced the proliferation rate of D54MG cells (human glioblastoma cells) while increasing the rate of cell death [68].…”
Section: Therapeutic Functionalitymentioning
confidence: 99%
“…In many cases, the use of both inorganic and organic components (nanocomposites) results in effective nanostructure-based theranostic systems [65]. All of these strategies have been combined with increasing selectivity, biocompatibility, cytocompatibility, and greater permeability of the BBB for the treatment of GBM [66].…”
Section: The Use Of Nanotechnology For Brain Tumor Diagnosis and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…It reduces cell proliferation along with an increase in cell death rates in human glioma cells. [ 27 ]…”
Section: N Anocarrier P Latforms For B Rain D Eliverymentioning
confidence: 99%